Toward precision psychiatry: theoretical implications of bimodal response patterns to vasopressin V1b receptor inhibition in depression - zu Eulenburg, Christine; Gehrlach, Daniel; Myhsok, Marius; Strote, Caren; Arvastson, Lars; Mueller-Myhsok, Bertram; Griebel, Guy; Eriksson, Hans (Frontiers in Psychiatry, 2025)
IntroductionDespite extensive research and numerous available treatments, major depressive disorder (MDD) remains a significant global health issue with limited efficacy from current monoaminergic antidepressants. Dysfunction in the hypothalamic–pituitary–adrenal (HPA) axis has been implicated in a subgroup of depressed patients, leading to interest in developing targeted treatments such as vasopressin V1b receptor antagonists. Nelivaptan, a potent V1b antagonist, demonstrated statistically significant antidepressant efficacy in one of two previous Phase 2 trials but was not pursued further.MethodsWe reanalyzed the trial data (NCT00358631) using a finite mixture of linear regression model (FMM) to investigate whether antidepressant responses to nelivaptan exhibit a bimodal distribution, suggesting distinct responder subgroups. We analyzed the 17-item Hamilton Rating Scale for Depression (HAMD) scores from baseline to day 56 for patients treated with 250 mg BID nelivaptan (n = 62) versus placebo (n = 63).ResultsOur analyses revealed a bimodal response distribution exclusively in the nelivaptan-treated group, characterized by two distinct subpopulations: a high-responder subgroup (mean change: −17.14) and a low-responder subgroup (mean change: −3.85). In contrast, the placebo group displayed a unimodal distribution (mean change: −7.06).DiscussionThese findings support the hypothesis that nelivaptan effectively reduces depressive symptoms specifically in a subset of MDD patients, potentially identifiable by underlying HPA axis dysfunction. The confirmation of this hypothesis requires further studies integrating measures of HPA axis activity alongside response to nelivaptan treatment, facilitating precision psychiatry approaches for depression.